Cycling performance and training load: Effects of intensity and duration - Kesisoglou, A.; Nicolò, A.; Passfield, L. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To examine the effect of cycling exercise intensity and duration on subsequent performance and to compare the resulting acute performance decrement (APD) with total work done (TWD) and corresponding training-load (TL) metrics. Methods: A total of 14 male cyclists performed a 5-minute time trial (TT) as a baseline and after 4 initial exercise bouts of varying exercise intensity and duration. The initial exercise bouts were performed in a random order and consisted of a 5- and a 20-minute TT and a 20- and a 40-minute submaximal ride. The resulting APD was calculated as the percentage change in 5-minute TT from baseline, and this was compared with the TWD and TL metrics for the corresponding initial exercise bout. Results: Average power output was different for each of the 4 initial exercise bouts (eta2p=.971; P < .001), and all bouts resulted in an APD. But APD was only different when comparing maximal with submaximal bouts (eta2p=.862; P < .001). The APD contradicted TWD and TL metrics and was not different when comparing 5- and 20-minute maximal TTs or the 20- and 40-minute submaximal bouts. In contrast, TL metrics were different for all training sessions (eta2p=.970; P < .001). Conclusion: An APD is found after initial exercise bouts consisting of 5- and 20-minute TTs and after 20- and 40-minute of submaximal exercise that is not consistent with the corresponding values for TWD or TL. This discrepancy highlights important shortcomings when using TWD and TL to compare exercise bouts of different intensity and duration.